Early legal careers in comparative context: evidence from Canada and the United States. Issue 1 (2nd January 2016) - Dinovitzer, Ronit; Dawe, Meghan
Abstract: This paper explores early careers by drawing on nationally representative surveys of lawyers' early careers in Canada and the United States. It will examine the sorting of lawyers in sectors and settings as well as the mechanisms that are key to understanding this process. Prior research has pointed to the importance of law school credentials, race, gender and social class, which continue to be important lines of demarcation. The comparative lens provides the opportunity to better understand the ways in which these factors are contingent on national context, which, in turn, shapes the symbolic and cultural value of the forms of capital that can provide access to more prestigious, powerful and remunerative positions in the legal profession.